Ethnopharmacological uses and public knowledge regarding Cinnamomum zeylanicum in Khobar, Saudi Arabia - Hanine Almubayedh; Rizwan Ahmad; Atta A Naqvi; Niyaz Ahmad (Journal of Pharmacy and Bioallied Sciences, 2018)
Background: Cinnamon (Cinnamomum zeylanicum) is a herb that is used traditionally as a flavoring agent as well as for its health benefits in different parts of the world. Its use may vary among cultures. Aim: To observe the knowledge and uses regarding cinnamon in the Saudi population. Materials and Methods: A 2-month cross-sectional study was conducted in Khobar, Saudi Arabia, using a novel questionnaire in Arabic language. Results: A total of 585 responses were collected. Most respondents were female (91.5%), adults (74.4%), married (65.6%), and had bachelor’s degree (58.1%). A total of 84.3% knew about cinnamon and used cinnamon as bark (38.6%) and as a flavoring agent (74.7%). Most common reason for use was to ease menstruation and menstrual pain (49.9%), as antidiabetic (35.9%), and for weight loss (5.6%). The source of information for cinnamon use and its knowledge was family and relatives who were using cinnamon (75.9%), that is, folkloric use. Conclusion: Folkloric use of cinnamon was found to influence the knowledge and usage of cinnamon in the Saudi population.